Mirror, mirror [large type] - Robb, J. D., 1950-; Blayney, Mary; Fox, Elaine; McComas, Mary Kay; Ryan, R. C., 1937- (Thorndike Press, A part of Gale, Cengage Learning, 2013)
Once upon a time... in a world far removed from the days when fairy tales were new, five bestselling authors spin versions that take the classic stories into a new dimension. You'll recognize Hansel and Gretel, Cinderella, the Little Match Girl, and other enduring characters -- but they'll exist in realms beyond your imagination, where the familiar is transformed into the extraordinary and otherworldly.